ELECTROPHYSICAL PROPERTIES OF HIGHER MANGANESE SILICIDE FILMS TO SILICON - N. F. Zikrillaev, T. S. Kamilov; I. M. Kokanbaev, A. Zh.Khusanov; K. K. Abdurafikov (Galaxy International Interdisciplinary Research Journal, 2022)
Investigation of the injection phenomenon in compensated semiconductors , in particular , silicon doped with different lines Impurity atoms, which create deep energy levels in the band gap, provide valuable and useful information about the nature of these levels, as well as for determining the mechanism of so far passage in such materials . This work is devoted to obtaining injecting contacts based on silicon doped with impurity manganese atoms. To receive engineering contacts and a plate of industrial silicon KDB-2, KDB-7.5 and KDB-10 with a diameter of 76 mm was used in part of the original material. Diffusion of boron or phosphorus into silicon was carried out from a solid source of nigridboron BN and phosphorus pentoxide . Controls the temperature of diffusion, the structures were found to be based on both hole and electronic conductivity with a number of different values of resistivity. The obtained results of the study allow creating injection contacts, the technology of which approaches the setting conditions, which makes it possible to create various semiconductor devices based on silicon doped with impurity manganese atoms.